Implementasi Client- Server Pada Sistem Informasi Manajemen Gereja Di Gereja Katolik Paroki Santa Maria Ratu Damai, Tomohon Selatan - Maydupi Astri Turnip; Quido C. Kainde; Alfiansyah Hasibuan (Riset Sinergi Indonesia (RISINDO), 2026)
The development of information technology opens opportunities for religious institutions to improve the quality of administration and pastoral care. At the Santa Maria Ratu Damai Catholic Church in South Tomohon, congregational data, finances, activities, and documents are still managed using standalone applications. This situation creates various obstacles, such as data inconsistency, limited access, and reporting delays. This study aims to design and develop a church management information system based on a client-server architecture as a solution to these problems. The system was developed using the Rapid Application Development (RAD) method, with Python Flask on the server side, MySQL as the database, and PyQt as a desktop application on the client side. The results of the study indicate that the resulting system is able to centrally integrate congregational data, finances, activities, announcements, documents, and organizational structures. Blackbox testing demonstrated that all features functioned as intended. Furthermore, validity and reliability tests on the effectiveness of the system produced valid and reliable values, so the system is considered suitable for use. The implementation of this system has been proven to increase efficiency, accuracy of data recording, digital document storage, and improve the quality of church administrative services.